2014
DOI: 10.5194/acp-14-3533-2014
|View full text |Cite
|
Sign up to set email alerts
|

Trends of road dust emissions contributions on ambient air particulate levels at rural, urban and industrial sites in southern Spain

Abstract: Abstract. The impact of road dust emissions on PM10 and PM2.5 (atmospheric particulate matter with diameteer < 10 μm and 2.5 μm mass concentrations recorded from 2003 to 2010 at 11 locations (rural, urban and industrial) in southern Spain was estimated based on the chemical characterization of PM and the use of a constrained Positive Matrix Factorization, where the chemical profile of local road dust samples is used as a priori knowledge. Results indicate that road dust increased PM10 levels on average by 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 32 publications
(32 reference statements)
4
57
1
1
Order By: Relevance
“…The concentration of PM 10 and PM 2.5 at present site is also compared with studies reported at other sites (Table 1). It has been seen that the concentration at the present suburban site is higher than the urban, and rural sites of the Spain (Amato et al 2014) while lower than the suburban site of China (Li et al 2008). The high load of aerosol in India may be due to the fact that India is a developing country while the Spain is a developed where proper attention has been given to concern of air pollution.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The concentration of PM 10 and PM 2.5 at present site is also compared with studies reported at other sites (Table 1). It has been seen that the concentration at the present suburban site is higher than the urban, and rural sites of the Spain (Amato et al 2014) while lower than the suburban site of China (Li et al 2008). The high load of aerosol in India may be due to the fact that India is a developing country while the Spain is a developed where proper attention has been given to concern of air pollution.…”
Section: Discussionmentioning
confidence: 82%
“…Matthias-Maser and Jaenicke (1995) stated that over Amazon rainforest, bioaerosol account for as much as 74 % of the total aerosol number concentration, with fungal spores contributing 30-50 %. Although biological components contribute 20 % load of aerosol, the biological fraction of ambient particulate matter can potentially cause significant health effects (Schneider et al 1997;Miguel et al 1999;Boreson et al 2004;Lee et al 2012;Amato et al 2014). Indo-Gangetic plain is experiencing a very drastic change in seasonal patterns with extreme cold in winter, extreme hot periods in the summer, and small monsoon periods with reduced rain events, increase of the aerosol loading in the last few decades, and increase of different epidemic diseases, e.g., malaria, typhoid, pneumonia, chickengunia, and monkeygunia and respiratory and cardiovascular diseases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In its emissions profile database (SPECIATE 4.0), the United States Environmental Protection Agency (EPA) presented a composite of five paved road dust profiles from the cities of San Antonio and Laredo, Texas (BVPVRD01, BVPVRD02, BVPVRD03, BVPVRD04 and BVPVRD05). Amato et al [27] analyzed road dust at different sites in Spain and compiled a profile for an urban site in the city of Seville. Table 4 compares the urban profile for the MASP (derived from the present study), the EPA composite urban profile, and the urban profile for Seville.…”
Section: Resultsmentioning
confidence: 99%
“…Estimated emission factors showed values within 39-137 mg VKT −1 (vehicle kilometer travelled −1 ), with a mean value of 63 mg VKT −1 , in the central range observed across Europe [40,41,67]. For OC and EC, mean emission factors due to resuspension were 5.0 and 1.4 mg VKT −1 , respectively.…”
Section: Road Dust Emissionsmentioning
confidence: 93%
“…Sedimented road dust with a diameter <10 microns (RD10) loadings showed small spatial variability across the sampling sites (0.68-1.35 mg · m −2 ) and in the lower range of European cities [40,41,67]; an exception was site 10, where the higher value (3.2 mg · m −2 ) was probably due to the poor state of the pavement. Based on the formula proposed by [40], the emission factors (EFs) were calculated as (Equation (13)):…”
Section: Road Dust Emissionsmentioning
confidence: 99%